MODL-11. COMPARISON OF HUMAN & MURINE PA/PXA CHARACTERISTICS. (4th December 2020) - Sommerkamp, Alexander C; Sun, Pengbo; Wefers, Annika K; Ismer, Britta; Schramm, Kathrin; Wittmann, Andrea; Gronych, Jan; Korshunov, Andrey; von Deimling, Andreas; Jäger, Natalie; Pfister, Stefan M; Jones, David T W
Abstract: Pediatric low-grade gliomas (pLGGs) are the most common brain tumors in children. Despite recent advances in the molecular characterization of this heterogeneous set of tumors, the separation of specific tumor types is still not fully established. Pilocytic astrocytoma (PA; WHO grade I) and pleomorphic xanthoastrocytoma (PXA; WHO grade II) are two pLGG types that can be difficult to distinguish based on histology alone. Even though their clinical course is different, they are often grouped as 'pLGG' in clinical trials (and therefore treated similarly). Based on a cohort of 89 human pediatric tumor samples, we show that PAs and PXAs have clearly distinct methylation and transcriptome profiles. The difference in gene expression is mainly caused by cell cycle- and development-associated genes, suggesting a key difference in the regulatory circuits involved in tumor growth. In addition to BRAF V600E, we found NTRK fusions and a previously unknown EGFR:BRAF fusion as mutually exclusive driving events in PXAs. Both tumor types show marked signs of immune cell infiltration, but with significant qualitative differences, which might represent therapeutic vulnerabilities. To pave the way for further research on PA and PXA, we developed corresponding mouse models using the virus-based RCAS system, which allows introduction of an oncogenic driver into immunocompetent mice for molecular and preclinical research. The murine tumors do not only histologically resemble their human counterparts but also show a similar growth behavior. Expression analysis revealed that the murine PXAs have a stronger gene signature of proliferation and immune cell infiltration compared to PAs.